Kemampuan Menulis Drama Siswa Kelas VIII SMP Negeri 12 Tasikmalaya - Aas Salamah; Dinda Nurdiana; Widyanti Kusuma; Adita Widara Putra (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research is research that aims to determine the ability to write drama scripts for class VIII K students at SMP Negeri 12 Tasikmalaya. This research uses a qualitative descriptive method with the source of the data obtained through observation and direct observation in the field. The data collection techniques used are observation and data assessment. The research results show that class VIII K students at SMP Negri 12 Tasikmalaya are in the good category with an average score of 84%.